Proteomic and metabolomic analysis of serum in women infected with COVID-19 during late pregnancy - Zheng, Yi; Ning, Jinyu; Zhu, Jiang; Zhu, Honglin; She, Zhihua; Cai, Pei (Frontiers in Immunology, 2025)
IntroductionTo investigate the alterations of serum proteins and metabolomics in women infected with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) at the end of pregnancy and their potential effects on fetal development.MethodsThe corona virus disease 2019 (COVID-19) group (n=31) included women in the third trimester diagnosed with SARS-CoV-2 infection and who delivered, while the control group (n=30) comprised uninfected women in the same gestational period. This study applied data-independent acquisition (DIA) proteomics and ultra-performance liquid chromatography coupled with quadrupole time-of-flight mass spectrometry (UPLC-Q-TOF-MS) metabolomics to analyze serum samples from two groups of full-term pregnant women. Serum samples in the control group were collected one week before delivery, while those in the COVID-19 group were collected within two days after the onset of fever. The differences between groups were compared by bioinformatics data analysis. For proteins and metabolites exhibiting a significant association with SARS-CoV-2, metabolic pathway enrichment was performed utilizing MetaboAnalyst 6.0, and the possible targets and pathways of SARS-CoV-2 infection in women in late pregnancy were plotted.ResultsThe incidence of cesarean section, postpartum reproductive tract infection, and fetal distress were significantly higher in the COVID-19 group compared to the control group. Differential proteomic analysis revealed the regulation of proteins such as SAA1, SAA2, IPO7, WDR19, and BAZ1A, which were involved in processes such as visual, skin and limb development. Metabolomics analysis revealed key altered metabolites, including 1-(7-methoxy-2-oxo-2H-chromen-8-yl)-3-methyl-2-oxobutylacetate, 5-(hydroxymethyl) -4-methoxy-2,5-dihydrofuran-2-one, and cyclocytidine, which were involved in the riboflavin metabolism, the phenylalanine, tyrosine and tryptophan biosynthesis, and the arginine biosynthesis. Integrative analysis of proteomic and metabolomic revealed significant disruptions in metabolic pathways, including arginine biosynthesis, steroid hormone biosynthesis, and fatty acid degradation.ConclusionsThis study revealed the main proteomic and metabolic effects of SARS-CoV-2 infection on women in the third trimester of pregnancy. Our comprehensive omics data elucidating the molecular mechanisms underlying SARS-CoV-2 infection in women during late pregnancy. These findings offer novel insights and potential targets for future investigations into the impact of SARS-CoV-2 infection on maternal and infant health.